ON THE STUDY OF THE MEANS OF SPEECH EXPRESSIVENESS OF THE UZBEK LANGUAGE - Fattakhova D.A. (Scholar Express Journals, 2022)
The article deals with the problem of teaching and developing the skills of teaching Russian-speaking students to use the means of speech expressiveness in speech, for the correct, accurate and emotional expression of thought. The article also reveals the meaning of such concepts as culture of speech, expressiveness of speech, accuracy, logic. Information is given about the figures, which are analyzed by specific examples
Keywords: speech culture; expressiveness; trope; figure